Tongue squamous cell carcinoma-derived exosomes miR-21-5p affect tumor progression via promoting M2 macrophage polarization - Zixian Xu; Xin Fang; Shan Wang; Jiabei Mu; Qixian Gai; Yantong Chen; Zheyi Sun; Jiemei Zhai (Non-coding RNA Research)
Exosome-mediated intercellular communication plays a key role in shaping the tumor microenvironment and promoting tumor progression. Recent studies have demonstrated that tumor exosomal miRNAs significantly contribute to the polarization of tumor-associated macrophages (TAMs). However, the molecular mechanisms underlying miRNA-mediated regulation of macrophage polarization by exosomes derived from tongue squamous cell carcinoma (TSCC) remain incompletely elucidated. In this study, small RNA sequencing analysis of exosomal miRNAs revealed miR-21-5p was highly expressed in TSCC-derived exosomes. Further investigation demonstrated a significant association between exosomal miR-21-5p and M2 polarization of tumor-associated macrophages (TAMs). Functionally, TSCC-derived exosomes promoted the polarization of M0 macrophages towards the M2 phenotype. Mechanistically, exosomal miR-21-5p enhanced M2 polarization of TAMs by inhibiting phosphorylation of ERK1/2. Additionally, we performed single-sample gene set enrichment analysis (ssGSEA), constructed a multivariate Cox regression model, and performed survival analysis using paired RNA transcriptome and clinical data from TSCC patients. Our results revealed a significant enrichment of M2 macrophages in the tumor microenvironment (TME) of TSCC compared to adjacent normal tissue. Furthermore, we confirmed that M2 macrophages infiltration is associated with poor prognosis in TSCC patients. In summary, our study demonstrates that TSCC-derived exosomal miR-21-5p plays an critical role in M2 macrophage polarization, and M2 macrophages infiltration contributes to the progression of TSCC. Therefore, these findings suggest that therapeutic targeting of miR-21-5p may represent a novel strategy for TSCC treatment by selectively modulating the M2 polarization of TAMs.